Does better pre-migration performance accelerate immigrants' wage assimilation? - Boris Hirsch; Elke J. Jahn; Ott Toomet; Daniela Hochfellner (Institute for the Study of Labor (IZA), 2013)
This paper analyzes wage assimilation of ethnic German immigrants to Germany. We use unique administrative data that include a standardized measure of immigrants' pre-migration wage based on occupation, industry, tenure, qualification, and the German wage structure. We find that immigrants experience a substantial initial wage disadvantage compared to natives. During their first 15 years in the host country they manage to close a considerable part of this gap, though assimilation is only partial. A 10% higher pre-migration wage translates into a 1.6% higher wage in Germany when also controlling for educational attainment, thus pointing at partial transferability of human capital acquired in the source country to the host country's labor market. We also find that wage assimilation is significantly accelerated for immigrants with a higher pre-migration wage. Our results are in line with strong complementarities between general skills and host country-specific human capital, in particular proficiency in the host country's language.
Keywords: J61; J31; J24; 330; migration; labor market assimilation; ethnic Germans; transferability of human capital